Monitoring the gelation time and curing process of a reinforced polyester lining - original data - Kharazmi, Parastou (Royal Institute of Technology, 2019)
Polymer linings used in sewer rehabilitation technologies are expected to cure fast in order for the renewed line to return to the service quickly and with minimum disruption. This dataset includes the original data obtained from the thermal analyses of a reinforced polyester composite used as pipe lining, including studying gelation, enthalpy and curing process for a better understanding of the material's curing behavior after application in the field.

The dataset was originally published in DiVA and moved to SND in 2024.

Polymer linings used in sewer rehabilitation technologies are expected to cure fast in order for the renewed line to return to the service quickly and with minimum disruption. This dataset includes the original data obtained from the thermal analyses of a reinforced polyester composite used as pipe lining, including studying gelation, enthalpy and curing process for a better understanding of the material's curing behavior after application in the field.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Monitoring the gelation time and curing process of a reinforced polyester lining - original data
Keywords: composites; kompositer; buildings; byggnader; polyester; polyester; Surface- and Corrosion Engineering; Yt- och korrosionsteknik; Polymer Technologies; Polymerteknologi; Composite Science and Engineering; Kompositmaterial och kompositteknik; Textile, Rubber and Polymeric Materials; Textil-, gummi- och polymermaterial